Hormone Replacement Therapy and Opioid Tapering for Opioid-Induced Hypogonadism Among Patients with Chronic Noncancer Pain: A Systematic Review. Issue 2 (2nd May 2018) - AminiLari, Mahmood; Manjoo, Priya; Craigie, Samantha; Couban, Rachel; Wang, Li; Busse, Jason W
Abstract: Objective: To systematically review evidence addressing the efficacy of testosterone replacement therapy (TRT) and opioid tapering for opioid-induced hypogonadism among patients with chronic noncancer pain. Study Design: Systematic review of randomized controlled trials (RCTs) and observational studies. Methods: We searched MEDLINE, CINAHL, AMED, CENTRAL, CINAHL, DARE, EMBASE, and PsycINFO through August 2017. Eligible studies enrolled ≥10 patients with chronic noncancer pain and opioid-induced hypogonadism and reported the effect of TRT or opioid tapering on a patient-important outcome collected ≥14 days after treatment. Pairs of reviewers independently screened for eligible studies, assessed risk of bias, and extracted data. We used the GRADE approach to rate quality of evidence. Results: Of 666 abstracts reviewed, five studies including one RCT (N = 84) and four observational studies (N = 157) were eligible. No studies explored the effect of opioid tapering for opioid-induced hypogonadism. Very low-quality evidence found that TRT was associated with improvements in pain (median reduction of 2 points on the 11-point numerical rating scale for pain; 95% confidence interval [CI] = –1.4 to –2.6; minimally important difference [MID] = 2 points), and emotional functioning (mean increase of 9 points on the 100-point SF-36 Mental Component Summary score; 95% CI = 4.40 to 13.60; MID = 5 points). Low-quality evidence suggested that TRT had no effect on sleep quality, sexual function, physical functioning, role functioning, or social functioning; very low-quality evidence suggested no association with depressive symptoms. Conclusions: Low-quality to very low-quality evidence suggests that TRT may improve pain and emotional functioning, but not other outcomes, in chronic noncancer pain patients with opioid-induced hypogonadism.